2000
DOI: 10.1016/s0550-3213(99)00632-x
|View full text |Cite
|
Sign up to set email alerts
|

(F,Dp) bound states from the boundary state

Abstract: We use the boundary state formalism to provide the full conformal description of (F,Dp) bound states. These are BPS configurations that arise from a superposition of a fundamental string and a Dp brane, and are charged under both the NS-NS antisymmetric tensor and the (p+1)-form R-R potential. We construct the boundary state for these bound states by switching on a constant electric field on the world-volume of a Dp brane and fix its value by imposing the Dirac quantization condition on the charges. Using the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
121
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(126 citation statements)
references
References 28 publications
5
121
0
Order By: Relevance
“…A precise relation between such a background and the boundary state has been established in Refs. [6,7]. There it has been shown that if one multiplies the massless tadpoles of |Dp by free propagators and then takes the Fourier transform, one gets the leading term in the large distance expansion of the classical p-brane solutions carrying Ramond-Ramond charges which are non-perturbative configurations of Type II or Type I supergravity.…”
Section: Introductionmentioning
confidence: 99%
“…A precise relation between such a background and the boundary state has been established in Refs. [6,7]. There it has been shown that if one multiplies the massless tadpoles of |Dp by free propagators and then takes the Fourier transform, one gets the leading term in the large distance expansion of the classical p-brane solutions carrying Ramond-Ramond charges which are non-perturbative configurations of Type II or Type I supergravity.…”
Section: Introductionmentioning
confidence: 99%
“…(2.26) is a mathematically rigorous statement, it will play a fundamental rôle even if our scenario might not be so accurate. For example, in [29], it was argued that the asymptotic behavior of 1 L 0 +L 0 |B coincides with the supergravity solution at the linear level. However, at the nonlinear level, it is easy to see that it fails to be the solution of HIKKO's equation of motion.…”
Section: Discussionmentioning
confidence: 99%
“…The projector which extracts the relevant emission mode is studied recently in ref. [8]. In our language, the modes in V relevant for the massless emission is only the constant part (since if one excite α creation operator, the state becomes massive).…”
Section: Correction To the D-brane Actionmentioning
confidence: 97%